2021
DOI: 10.1108/jicv-11-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Forward collision warning system for motorcyclist using smart phone sensors based on time-to-collision and trajectory prediction

Abstract: Purpose The purpose of this paper is to develop a proof-of-concept (POC) Forward Collision Warning (FWC) system for the motorcyclist, which determines a potential clash based on time-to-collision and trajectory of both the detected and ego vehicle (motorcycle). Design/methodology/approach This comes in three approaches. First, time-to-collision value is to be calculated based on low-cost camera video input. Second, the trajectory of the detected vehicle is predicted based on video data in the 2 D pixel coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Tang and Li [ 147 ] propose ‘End-to-End Monocular Range Estimation’ for collision warning. Lim et al [ 148 ] created a ‘Forward Collision Warning System for Motorcyclists’ using smartphone sensors. Farhat, Rhaiem, Faiedh, and Souani [ 149 ] present a ‘Cooperative Forward Collision Avoidance System Based on Deep Learning’.…”
Section: Discussion—methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Tang and Li [ 147 ] propose ‘End-to-End Monocular Range Estimation’ for collision warning. Lim et al [ 148 ] created a ‘Forward Collision Warning System for Motorcyclists’ using smartphone sensors. Farhat, Rhaiem, Faiedh, and Souani [ 149 ] present a ‘Cooperative Forward Collision Avoidance System Based on Deep Learning’.…”
Section: Discussion—methodologymentioning
confidence: 99%
“…Tang et al [147] introduce a monocular range estimation system using a single camera for precise FCWS, especially in difficult scenarios. Lim et al [148] suggest a smartphone-based FCWS for motorcyclists utilizing phone sensors to predict collision risks. Farhat et al [149] [150] propose a 'Lightweight Collaboration of Detecting and Tracking Algorithm' for embedded systems.…”
Section: Search Terms and Recent Trends In Fcwsmentioning
confidence: 99%
“…Object recognition plays a significant role in intelligent transportation systems, serving as both a crucial technical method and a fundamental link between high-level tasks such as target tracking and behavior recognition. It is an important research field within computer vision, aiming to efficiently identify vehicle targets and extract relevant feature information from static or dynamic videos using machine learning, AI, pattern recognition, image processing, and other technologies (Lim et al, 2021). Its wide application and research value can be observed in areas such as intelligent transportation, vehicle tracking, and unmanned driving, among others.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, drivers changing lanes dangerously often causes traffic flow turbulence and may even lead to traffic accidents [1,2]. Traffic accidents caused by lane changes account for 5% of the total number of accidents, including 75% caused by drivers changing lanes dangerously [3]. Statistics from the National Highway Traffic Safety Administration (NHTSA) show that approximately 240,000 to 610,000 traffic accidents are caused by drivers changing lanes each year, and at least 60,000 people are injured in traffic accidents caused by lane changes [4].…”
Section: Introductionmentioning
confidence: 99%